Digestibility of a Structural Fat Consisting of Stearic and Palmitic Acid in Dogs - Yuangklang, Chalermpon; Vasupen, Kraisit; Wongsuthavas, Sasiphan; Beynen, Anton C. (Journal of Mahanakorn Veterinary Medicine, 2016)
It was speculated that a structured fat consisting of stearic and palmitic acid would have sufficiently low digestibility that it could serve as functional ingredient in a very-low energy, weight-reduction diet for dogs. The fatty-acid moiety of the structured fat under study contained 55 % stearic acid and 44 % palmitic acid. In a feeding trial with dogs, the apparent digestibility of the structured fat was determined by the difference method and compared with that of palm oil. In a 3x3 Latin square-design, 11 dogs were fed a commercial dry food without or with 10% added palm oil or structured fat. The digestibility of palm oil was found to be 96.6 % and that of the structured fat was 68.8 %. It is concluded that the digestibility of the structured fat is too high for the formulation of a very-low energy, canine weight-reduction diet. The addition to the diet of the structured fat, instead of palm oil, increased the amount of feces. This was caused by a lower apparent digestibility of dietary dry matter, due to the low digestibility of the structured fat and a decrease in the digestibility of non-structural carbohydrates.